Cervantes across the centuries. A quadricentennial volume edited by Angel Flores and M. J. Benardete. New York, The Dryden Press, 1947, X+ 374 páginas. Homenaje a Cervantes. En Realidad, Buenos Aires, octubre de 1947, vol. ii, n° 5. - Alonso, Amado (El Colegio de México, 2007)
Se reseñó el libro: Cervantes across the centuries. A quadricentennial volume edited by Angel Flores and M. J. Benardete.